The Influence of Price and Promotion on Purchasing Decisions in the Shopee Marketplace : Case Study on People Aged 20-25 in Makassar City - Lukman S; Akhtar, M; Agusman Aris, Affandy; Hartini, Hartini (Jurnal Manajemen (Edisi Elektronik), 2024)
This study aims to determine and analyse: the effect of price on purchasing decisions; the effect of promotion on purchasing decisions; and the effect of price and promotion on purchasing decisions. This type of research is quantitative research with a causal associative approach. The study sample consisted of 70 respondents aged 20 – 25 in Makassar. Data collection techniques using questionnaires and documentation techniques. Data analysis techniques are carried out after data from all respondents or other data sources are collected with analytical activities including test prerequisite analysis and hypothesis testing (multiple linear regression). Through instrument and data quality tests (validity test and reliability test), classic assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, t-test, F test, coefficient of determination. The results of the study show that: price had a positive and significant effect on purchasing decisions in marketplace Shopee with a significance value is 0,000 > 0,05; promotion had a positive and significant effect on buying decisions in marketplace Shopee with a significance value is 0,008 > 0,05; and overall, price and promotion had a positive and significant effect on purchasing decisions in marketplace Shopee with significance value is 0,000 > 0,05..